Sign multilingualism - Zeshan, Ulrike; Webster, Jennifer (Sign language typology series ;, 2020)
This volume has arisen from a three-part, five-year study on language contact among multilingual sign language users, which has three strands: cross-signing, sign-switching, and sign-speaking. These phenomena are only sparsely documented so far, and thus the volume is highly innovative and presents data and analyses not previously available.